2012
DOI: 10.3945/jn.111.149575
|View full text |Cite
|
Sign up to set email alerts
|

Sweetness and Food Preference

Abstract: Human desire for sweet taste spans all ages, races, and cultures. Throughout evolution, sweetness has had a role in human nutrition, helping to orient feeding behavior toward foods providing both energy and essential nutrients. Infants and young children in particular base many of their food choices on familiarity and sweet taste. The low cost and ready availability of energy-containing sweeteners in the food supply has led to concerns that the rising consumption of added sugars is the driving force behind the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
155
1
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 265 publications
(179 citation statements)
references
References 91 publications
9
155
1
14
Order By: Relevance
“…Innate food preferences probably evolved in an environment where food scarcity was a constant risk. An intrinsic desire for energy-dense and nutrient-rich food, such as meat, once promoted survival but today may predispose us to the diseases of overconsumption (17,18).…”
Section: Drivers Of Meat Consumptionmentioning
confidence: 99%
“…Innate food preferences probably evolved in an environment where food scarcity was a constant risk. An intrinsic desire for energy-dense and nutrient-rich food, such as meat, once promoted survival but today may predispose us to the diseases of overconsumption (17,18).…”
Section: Drivers Of Meat Consumptionmentioning
confidence: 99%
“…64 This result is in agreement with other studies pointing out that children typically select the most intensely sweet taste and the pleasure response to the sweet taste is observed in individuals of all ages, races and cultures. 65 However, several studies have shown that these initial preferences could be altered aer birth via early experiences with food and eating during the rst years of life. Parents' choices made at the beginning (for example feeding milk formula or breast-feeding) affect the development of food acceptance patterns in infants.…”
Section: Development Of Preferencesmentioning
confidence: 99%
“…Aroma may lead to the rejection of complementary food by infants if it turns out to be unattractive. Acceptance of food by infants has been shown to correlate with its taste, with sweetness being the most preferred [22,23]. Taste of porridge from the 6 initial blends ranged from "dislike slightly" to "like very much" and was in the order LR-6, LR-4, LR-1>LR-2>LR-3>LR5.…”
Section: Discussionmentioning
confidence: 99%